TLQP-21 is a low potency partial C3aR activator on human primary macrophages - Li, Xaria X.; Lee, John D.; Lee, Han S.; Clark, Richard J.; Woodruff, Trent M. (Frontiers in Immunology, 2023)
TLQP-21 is a 21-amino acid neuropeptide derived from the VGF precursor protein. TLQP-21 is expressed in the nervous system and neuroendocrine glands, and demonstrates pleiotropic roles including regulating metabolism, nociception and microglial functions. Several possible receptors for TLQP-21 have been identified, with complement C3a receptor (C3aR) being the most commonly reported. However, few studies have characterised the activity of TLQP-21 in immune cells, which represent the major cell type expressing C3aR. In this study, we therefore aimed to define the activity of both human and mouse TLQP-21 on cell signalling in primary human and mouse macrophages. We first confirmed that TLQP-21 induced ERK signalling in CHO cells overexpressing human C3aR, and did not activate human C5aR1 or C5aR2. TLQP-21 mediated ERK signalling was also observed in primary human macrophages. However, the potency for human TLQP-21 was 135,000-fold lower relative to C3a, and only reached 45% at the highest dose tested (10 μM). Unlike in humans, mouse TLQP-21 potently triggered ERK signalling in murine macrophages, reaching near full activation, but at 10-fold reduced potency compared to C3a. We further confirmed the C3aR dependency of the TLQP-21 activities. Our results reveal significant discrepancy in TLQP-21 C3aR activity between human and murine receptors, with mouse TLQP-21 being consistently more potent than the human counterpart in both systems. Considering the supraphysiological concentrations of hTLQP-21 needed to only partially activate macrophages, it is likely that the actions of human TLQP-21, at least in immune cells, may be mediated by pathways other than C3aR in humans.